Peningkatan Kemampuan Pemahaman Matematis Siswa Melalui Pembelajaran Kooperatif Tipe Rotating Trio Exchange - Yeni Nuraeni; Ekasatya Aldila Afriansyah (Jurnal Inovasi Pendidikan Dasar, 2016)
One of the abilities that need to be owned and developed by the students is the ability of understanding mathematics. This research aims to determine the comparison of the students’ understanding mathematical ability results that get a cooperative Rotating Trio Exchange (RTE) and traditional learning model. The method used was a quasi-experiment. Population were all of seven grade students at SMP Negeri 2 Garut. Two classes were selected randomly as the sample. One class as an experimental class and the other class as the control class. The research finding indicate that the experimental group learning using cooperative learning type of RTE better with an average increase of the pre-test and post-test of 15.42 to 42.24, while classroom learning control using traditional learning with an average increase of the pre-test and post-test of 14.93 to 32.93. Thus, students are learning with RTE better than students who learning with traditional learning.